AMPLIFIKASI GEN COI DARI SAMPEL DARAH ULAR DENGAN MENGGUNAKAN BEBERAPA PASANGAN PRIMER UNIVERSAL - Pahlevi, Dylan R.; de Queljoe, Edwin; Kolondam, Beivy J. (Universitas Sam Ratulangi, 2019)
AMPLIFICATION OF COI GENE FROM SNAKE BLOOD SAMPLES USING TWO UNIVERSALPRIMER PAIRS. This study aims to amplify COI (Cytochrome Oxidase Subunit I) gene fragments from snake blood. Four samples were obtained from four different snake individuals that were captured in Tapahan Telu Waterfall, Kali Village, Minahasa Regency. Total DNA from the sample was isolated and then the COI gene was amplified through the PCR (Polymerase Chain Reaction) reaction using two primer pairs, LCO1490-HCO2198 and FF2d-FR1d. These four samples were successfully amplified using different primers, i.e. DRP1 and DRP3 by FF2d-FR1d and DRP2 and DRP4 by LCO1490-HCO2198 primers. The success of amplification marked by the presence of 710 bp (LCO1490-HCO2198) and 707 bp (FF2d-FR1d) bands, which were indicated by those bands were located close to the standard 750 bp DNA ladder.Â Key words: Snake, Amplification, COI gene, Primers, PCR